1997
DOI: 10.1159/000237469
|View full text |Cite
|
Sign up to set email alerts
|

Mite-Induced Allergic Airway Inflammation in Guinea Pigs

Abstract: Background: Mites are the most common aeroallergen in human allergic asthma. However, no animal model of mite-induced allergic airway inflammation has been reported before. In this study, an animal model of mite-induced allergic airway inflammation in guinea pigs was developed. Methods: Firstly, we found that two intraperitoneal injections of 100 μg crude mite extract (CME), but not multiple aerosol inhalations of 10 mg/ml CME, can cause sensitization in guinea pigs. The sensitization to mites was confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Among the many aeroallergens, house dust mites are the most common [3], and any approach to the experimental study of house dust mite allergy to improve medical treatment requires a suitable animal model, such as the mouse or guinea pig [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Among the many aeroallergens, house dust mites are the most common [3], and any approach to the experimental study of house dust mite allergy to improve medical treatment requires a suitable animal model, such as the mouse or guinea pig [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the majority of work, in animal models, relating to allergy to HDM Ags has been performed in immunologically deficient animals in the form of a humanized SCID mouse model (8,9) or in either of the above-mentioned conventional models (10 -13). In this regard, Hsiue et al (14) showed that multiple aerosol inhalations of crude mite extract were insufficient to cause sensitization in guinea pigs and that, in fact, i.p. injections were required to elicit overt Th2 sensitization.…”
mentioning
confidence: 99%
“…In this study, aerosol challenge of intraperitoneally mite–sensitized animals caused eosinophilia in BAL fluid, which peaked 24 h after the aerosol challenge. Eosinophilia was generally sustained for at least 1 week, and subsided after 2 weeks [13]. …”
Section: Discussionmentioning
confidence: 99%
“…They were actively sensitized with an intraperitoneal injection of 100 µg CME with 4 mg Al(OH) 3 in 1 ml normal saline on days 0 and 7 [13]. …”
Section: Methodsmentioning
confidence: 99%